#### Answer

fill the blank with
... $\pi$ ...

#### Work Step by Step

For inverse functions,
$f(f^{-1}(y))=y$ and
$f^{-1}(f(x))=x.$
so,
$f^{-1}(-1)=f^{-1}(f(\pi))=\pi.$
fill the blank with
... $\pi$ ...

Published by
Pearson

ISBN 10:
013421742X

ISBN 13:
978-0-13421-742-0

fill the blank with
... $\pi$ ...

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.